Expanded acceptor substrates flexibility study of flavonol 7-O-rhamnosyltransferase, AtUGT89C1 from Arabidopsis thaliana. (11th December 2015) - Parajuli, Prakash; Pandey, Ramesh Prasad; Trang, Nguyen Thi Huyen; Oh, Tae Jin; Sohng, Jae Kyung
Highlights: We explore the expanded acceptor substrate flexibility of AtUGT89C1. We examine the catalytic potential of AtUGT89C1 using E. coli indigenous sugar. Library of flavonoids 7- O -rhamnoside could be produced using AtUGT89C1. Graphical abstract: Abstract: Acceptor substrates flexibility of previously characterized flavonol 7- O -rhamnosyltransferase (AtUGT89C1) from Arabidopsis thaliana was explored with an endogenous nucleotide diphosphate sugar and five different classes of flavonoids (flavonols, flavones, flavanones, chalcone and stilbenes) through a biotransformation approach. In contrast to the previous reports, this study highlights the expanded acceptor substrate promiscuity of AtUGT89C1 for the regiospecific glycosylation of diverse class of flavonoids at 7-hydroxyl position using microbial thymidine diphosphate (TDP)-l -rhamnose as sugar donor instead of uridine diphosphate-l -rhamnose. We examine the biocatalytic potential of AtUGT89C1 using endogenous sugar (TDP-l -rhamnose) from E. coli to generate a library of flavonoid 7- O -rhamnosides.